1997
DOI: 10.1038/sj.bjp.0701311
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the mechanisms underlying the hypophagic effects of the 5‐HT and noradrenaline reuptake inhibitor, sibutramine, in the rat

Abstract: 1 Sibutramine is a novel 5-hydroxytryptamine (5-HT) and noradrenaline reuptake inhibitor (serotoninnoradrenaline reuptake inhibitor, SNRI) which is currently being developed as a treatment for obesity. Sibutramine has been shown to decrease food intake in the rat. In this study we have used a variety of monoamine receptor antagonists to examine the pharmacological mechanisms underlying sibutramineinduced hypophagia. 2 Individually-housed male Sprague-Dawley rats were maintained on reversed phase lighting with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(122 citation statements)
references
References 26 publications
3
117
0
2
Order By: Relevance
“…Notably, the PVN is among the brain regions expressing the highest NE transporter (NET) binding level (Kung et al, 2004), which argues for tesofensine produced a blockade of NET function within the PVN, resulting in efficient accummulation of PVN synaptic NE favoring anorexic a 1 adrenoceptorinduced signaling. Specificity for a 1 adrenoceptor effects in the PVN after NET inhibition is further supported by the finding that sibutramine elevates synaptic NE levels in the PVN of lean rats, which is thought to be linked to its a 1 adrenoceptor antagonist-sensitive hypophagic effect (Jackson et al, 1997;Wortley et al, 1999).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Notably, the PVN is among the brain regions expressing the highest NE transporter (NET) binding level (Kung et al, 2004), which argues for tesofensine produced a blockade of NET function within the PVN, resulting in efficient accummulation of PVN synaptic NE favoring anorexic a 1 adrenoceptorinduced signaling. Specificity for a 1 adrenoceptor effects in the PVN after NET inhibition is further supported by the finding that sibutramine elevates synaptic NE levels in the PVN of lean rats, which is thought to be linked to its a 1 adrenoceptor antagonist-sensitive hypophagic effect (Jackson et al, 1997;Wortley et al, 1999).…”
Section: Discussionmentioning
confidence: 54%
“…For sibutramine, suppression of food intake could be partially reversed by simultaneous ritanserin or SB206553 administration, thus implicating 5-HT 2A/C or 5-HT 2B/C receptor activation (Jackson et al, 1997;Grignaschi et al, 1999;Balcioglu and Wurtman, 2000). It is suggested that the serotonergic effects of sibutramine on feeding and body weight may likely be ascribed to its primary and secondary amine metabolites, which are triple MRIs, rather than sibutramine per se (Heal et al, 1998;Glick et al, 2000;Nelson and Gehlert, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential cardiovascular risk of this compound is probably largely related to its adrenergic properties. The anti-obesity effects of sibutramine, however, are due to its effect on the serotonergic system, but alphaand beta-adrenoreceptors are also involved [341,342]. Assuming that only a modest weight loss will be achieved in many patients following a long period of taking the drug, safety becomes the most important issue for anti-obesity drugs.…”
Section: Serotonin and The Pharmacotherapy Of Obesitymentioning
confidence: 99%
“…In such a model, using Sprague-Dawley rats, Jackson et al, (1997) described the hypophagic effects of Sibutramine and identified the key adrenoreceptors and serotonergic receptors involved in its pharmacological mechanism. In a study to determine the safety of Sibutramine it was observed that, following Sibutramine 3 administration, ultrastructural changes in morphology associated with fibrosis in liver tissue in Sprague-Dawley rats fed a high energy diet that did not result in weight gain, could be observed by Oberholzer et al (2013).…”
Section: Introductionmentioning
confidence: 99%